The Effect Of Fundamental And Technical Variables On The Return Of Banking Share Listed On The Indonesia Stock Exchange For The 2017 – 2021 Period - Wahyu Kusuma Wijaya; Prasetyo Nugroho (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
The purpose of this study is to determine whether fundamental and technical variables have an effect either partially or simultaneously on stock returns in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This research was conducted in a quantitative descriptive manner using secondary data obtained from the financial statements of the Indonesia Stock Exchange (IDX). The population selected in this study were 47 companies banking companies, the sample was selected using purposive sampling method and obtained 30 companies that meet the criteria. The variables used in this study are EPS, DER, CR, TVA and stock prices as independent variables, stock returns as the dependent variable. Hypothesis testing in this study used t test (partial), F test (simultaneous) with SPSS (statistical product and service solutions) application tools. The results of this study prove that: (1) The results of fundamental analysis testing which include indicators of EPS, DER and CR indicate that the fundamental variables have no significant negative effect onstock returns (2) The results of technical analysis tests which include indicators of Stock Trading Volume (TVA) and Price Stocks show that technical variables have a positive and insignificant effect on stock returns. (3) Simultaneous test results show that EPS, DER, CR, Stock Trading Volume (TVA) and Stock Prices simultaneously have no significant effect on stock returns.